Aggressive Biting Behavior and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The biting behavior (BB) and other aggressive gestures in a group of 11 patients (8 male; 3 female) with drug-resistant seizures were studied in presurgical evaluations using video-EEG/SEEG monitoring at University of Bologna; Niguarda Hospital, Milan; and University of Modena, Italy.